Construction and preparation of nitrogen-doped porous carbon material based on waste biomass for lithium-ion batteries. (13th May 2021) - Yang, Xinxin; Zheng, Xuchao; Yan, Zhanheng; Huang, Zhongyuan; Yao, Yong; Li, Huanxin; Kuang, Yafei; Zhou, Haihui
Abstract: Biomass derived carbon materials have been widely studied as electrodes in energy storage devices due to their renewable nature, low-cost and tunable physical/chemical properties. However, the influences of different treatments for biomass derived carbon materials are still lack of in-depth discussion. In this work, we investigate the effects of the treatment for biomass on the structure and composition of the resulted carbon materials. Especially, the optimal N-doped porous carbon (NPCCS), which was fabricated by H2 SO4 -assisted hydrothermal treatment and subsequent pyrolysis process using corn silk as raw material, shows a unique interconnected layered nanostructure with ultra-high nitrogen content (18.79 at%). As a result, the NPCCS electrode displays excellent cycling stability and outstanding rate performance in lithium-ion half-cell test and shows high first reversible specific capacity of 523.6 mAh g −1 in full-cell test. This work provides some guidance for preparing biomass derived carbon materials with superior electrochemical performance for the applications in advanced energy storage devices. Highlights: Biomass derived carbon materials composed of N-doped carbon layers was synthesized. The hydrothermal treatment could corrode the biomass and introduce many pores. High lithium ions storage capacity and rate capability of NPCCS were confirmed. NPCCS showed great cyclic life and rate performance in lithium ion full batteries.